2015
DOI: 10.1007/s11096-015-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions experience in a teaching hospital in Jordan

Abstract: Jordanian healthcare providers should be aware of the importance of detecting and reporting ADRs, in order to prevent and reduce the incidence of ADRs. Awareness of risk factors predisposing to ADRs may help in identifying patients with higher risk and therefore reducing the risk of these ADRs and improving patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
4
8
1
1
Order By: Relevance
“…Consistent with other studies , we found that patients with ADRs tended to be older, were more likely to be admitted to a medical ward and received more drugs. However, many variables including age and number of drugs were eliminated in the final set of predictors because of collinearity with other variables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with other studies , we found that patients with ADRs tended to be older, were more likely to be admitted to a medical ward and received more drugs. However, many variables including age and number of drugs were eliminated in the final set of predictors because of collinearity with other variables.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that 8.1% of admissions were caused at least in part by an ADR is therefore consistent with these prior data. However, our finding that 12.4% of patients had an ADR at time of hospital admission is higher than what has been reported previously, namely 2.3–7.9% . Several factors likely contribute to this difference.…”
Section: Discussioncontrasting
confidence: 83%
“…On the other hand, consequences are outcomes of the concept, such as quality of life impairment, economic impact, death, hospital admission, and morbidity (Chen et al., ; Coleman & Pontefract, ; Onder et al., ; Su et al., ). Clinical manifestations can also be experienced, for example, acute renal failure, hypotension, arrhythmia, cutaneous reaction, gastrointestinal complaints, falls, electrolyte disorder, anemia, infections, and bleeding (Alsbou et al., ; Coleman & Pontefract, ; Davies et al., ; Muñoz‐Torrero et al., ; O'Connor, Gallagher, Byrne, & O'Mahony, ; Onder et al., ; Passarelli, Jacob‐Filho, & Figueras, ; Rashed et al., ; Shah et al., ; Smyth et al., ).…”
Section: Evaluation Of Findingsmentioning
confidence: 99%
“…The final step is determining the empirical referents, which demonstrate the occurrence of the concept in the clinical practice. Some articles used the same validated scale for evaluating the probability and causality of adverse reactions to medications (Alsbou et al., ; Andrade, Lobo, & da Silva, ; Shah, Gajjar, & Desai, ; Coleman & Pontefract, ; Davies et al., ; Harugeri, Parthasarathi, Ramesh, Guido, & Basavanagowdappa, ; Mandavi, D'Cruz, Sachdev, & Tiwari, ; Muñoz‐Torrero et al., ; Onder et al., ; Passarelli et al., ). One study identified variables associated with adverse reactions, such as number of medications and history of adverse reactions, and developed a risk score, which was validated in a sample of elderly patients (Onder et al., ).…”
Section: Evaluation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation